BENZYLISOQUINOLINE ALKALOIDS FROM BARK OF Cryptocarya rugulosa - Nurdin Saidi; Hiroshi Morita; Marc Litaudon; Mat Ropi Mukhtar; Khalijah Awang; A. Hamid A. Hadi (Indonesian Journal of Chemistry, 2011)
Seven known Benzylisoquinoline alkaloids, Papraline 1, (+)-norcinnamolaurine 2, (+)-codamine 3, (+)-6-methoxy-1-(3'-methoxybenzyl)-N-methyl-7-isoquinolinol 4, (+)-reticuline N-oxide 5, (+)-reticuline 6 and (-)-N-methylisococlaurine 7 were isolated from bark of Cryptocarya rugulosa. A combination of 1D-NMR (1H, 13C, DEPT, NOE), 2D-NMR (COSY, NOESY, HMQC, HMBC), MS (HRESI+, FAB+ and EI) spectroscopy used to elucidate the structure.